Issues and security measures of mobile banking apps - Hayikader, Sameer; Abd Hadi, Farah Nurafiqah Hanis; Ibrahim, Jamaludin (2016)
Mobile apps is a used to designate the act or process by which application software is developed for handheld devices, such as personal digital assistants or mobile phones. These applications can be pre-installed on phones during manufacturing platforms, or delivered as web applications using server-side or client-side processing (e.g. JavaScript) to provide an "application-like" experience within a Web browser. However there are some cases where the mobile internet banking apps occurred some problems that might cause loss of money. Therefore, in this paper we will examine issues on the architecture, and some security issues of mobile internet banking apps. And then we will explore some security measuras to deal with the associated security challenges.